Recent Synthetic Methodologies for Chalcone Synthesis (2013-2018) - Farooq, Saba; Ngaini, Zainab (Current Organocatalysis, 2019)
An up-to-date short review of the chalcone methodologies is presented, which is the most interesting and beneficial for choosing the desired protocol to synthesize suitable derivatives of chalcones. Chalcones are fluorescent, stable compounds which contribute to the synthesis of various pharmacologically important heterocyclic structure-based derivatives. Chalcone has displayed a remarkable curative efficiency to cure several diseases. Several schemes and methodologies have been reported for employing different catalysts and reagents. The development of improved methodologies of α, β-unsaturated carbonyl compounds is still on going. In this review, synthetic methodologies and their recent modification in designing new methods with efficient, economical, eco-friendly and high yield are discussed.
Keywords: indoline